Nilai Manugal dalam Budaya Dayak dan Relevansinya dalam Kehidupan Kristen: Kajian Teologi Kontekstual Model Budaya Tandingan - Riky Riky; Kana Kana; Richard Majefat; Sarmauli Sarmauli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research aims to examine the process of implementing the manugal tradition among the Dayak Ngaju community, identify the values contained within it, and analyze its relevance in Christian life thru a contextual theology approach of the counter-cultural model. This research uses a descriptive qualitative method with a literature review approach thru the collection of data from journals, books, and relevant scientific sources. The research results show that manugal is a rice planting tradition of the Dayak Ngaju community, carried out in stages, starting from meneweng, manyeha, mangakal, to the seed planting process using tugal communally (handep hapakat). This tradition not only serves as an agricultural activity but also embodies values of social solidarity, togetherness, care, responsibility, and dependence on God, which are manifested thru communal prayers before the implementation of manugal. In the perspective of Christian life, these values are relevant to the teachings of love, friendship, humility, mutual assistance, and the concept of the body of Christ living in harmonious relationships with others. In addition to having positive values such as character formation, strengthening social solidarity, and community spirituality, the manugal culture also has negative values, such as land burning practices that have the potential to harm the environment and the habit of consuming alcoholic beverages that need to be critically reviewed based on Christian faith values. Therefore, the manugal culture can be understood as a countercultural model to modern individualistic culture because it emphasizes values of togetherness, mutual assistance, and social concern, which still need to be theologically reflected upon to align with Christian teachings.